Difficulties faced by chronic dialysis patients in adolescence: Experience report (Research, Society and Development, 2023)
The experience report reports the student's trajectory in the field, in a Hemodialysis unit, in the state of Bahia, of a descriptive nature, with a qualitative approach. To reinforce the experience report, there was a collection in the database that began in February to June 2023 through a bibliographic survey of the databases on the internet, which are SCIELO and LILACS, using the Boolean operator "AND" . The following health descriptors (DeCS) were used to locate the studies: adolescents, hemodialysis, Chronic Kidney Disease. The present experience report has as a research problem: What are the difficulties faced by chronic dialysis patients in adolescence? With the objective: To describe the repercussions experienced by adolescents undergoing hemodialysis. In view of field observation, it was noted that adolescent patients faced difficulties in adapting to the life of illness in the face of hemodialysis treatment, restrictions and social issues. It is concluded that the main consequences for adolescents with CKD are related to the changes that hemodialysis causes in their lives, these changes are related to difficulties in relating to social media, restrictions and limitations caused by the treatment.